Synthesis, characterization, and magnetic studies of coordination polymers with Co(II) and Mn(II) ions - Ahmad, Musheer; Das, Raja; Lama, Prem; Poddar, Pankaj; Bharadwaj, Parimal K. (Crystal Growth & Design, 2012)
{An ether bridged tricarboxylic acid ligand, 5-(4-carboxybenzyloxy)isophthalic acid (p-cbiaH(3)) has been used to construct three coordination polymers with Co(II) salts in presence of different nitrogen donor ligands such as 1,4-bis(4-pyridinylmethyl)piperazine (bpmp), dipyridine-4-yl-diazene (dpd), and 4,4'-bipyridine (bpy). The products formed under hydrothermal conditions are formulated as {[Co-3(p-cbia)(2)(bpmp)(2)(H2O)(6)]center dot 10H(2)O}(n) (1), {[Co-2(p-cbiaH)(2)(dpd)(H2O)(2)]\